Studi Eksperimental Pengaruh Variasi Laju Udara Terhadap Kebutuhan Bakar Insinerator Limbah Medis Dual Chamber - Riski Ananta, I Gede; Suprapta Winaya, I Nyoman; Arya Darma, I Wayan; Angga Yuda Pratama, I Putu (Teknik Desain Mekanika, 2023)
Abstract An experimental study was conducted on a dual-chamber medical waste incinerator to determine the consumption rate and fuel requirements of medical waste and gas, with variations in the predetermined air flow rate. The tested samples consisted of 1 kg of medical waste for each sample. The incineration process was carried out for a duration of 3 minutes of burning, with an initial temperature set at 800°C in the first combustion chamber and an initial temperature of 1000°C in the second combustion chamber. The air flow rate variations used in this study were 8.02 m/s, 10.05 m/s, and 12.06 m/s. From the conducted tests, the highest consumption rate of medical waste fuel was obtained with the variation of 10.05 m/s, at 19.04 kg/h, while the lowest was at 8.02 m/s, at 18.66 kg/h. The consumption rate of gas fuel decreased from the first to the third variation, with the highest at 6.33 kg/h and the lowest at 6.13 kg/h. Keywords: Dual Chamber Incinerator, Air Supply, Fuel Consumption Rate.